2013
DOI: 10.1021/am303176a
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Robust Superhydrophobic Fabrics and Sponges from In Situ Growth of Transition Metal/Metal Oxide Nanocrystals with Thiol Modification and Their Applications in Oil/Water Separation

Abstract: Solid surfaces possessing both superhydrophobic and superoleophilic properties have attracted significant interest in fundamental investigations and potential applications in the fields of self-cleaning surfaces, oil/water separation, and microfluidic channels. In this paper, a general methodology for robust superhydrophobic fabrics and sponges was proposed via the in situ growth of both transition-metal oxides and metallic nanocrystals, including the simple neutralization reaction and oxidation-reduction reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
161
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 265 publications
(167 citation statements)
references
References 30 publications
2
161
0
2
Order By: Relevance
“…These materials have received increasing attention as an oil-absorbing material in oil/water separation for their microscale roughness in the integral fabric and their native porosity (Bi et al 2013;Wang et al 2013). Liu et al (2014) prepared superhydrophobic and superoleophilic SiO2-modified cotton for oil/water separation via a sol-gel process, which was initially pretreated by NaOH aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have received increasing attention as an oil-absorbing material in oil/water separation for their microscale roughness in the integral fabric and their native porosity (Bi et al 2013;Wang et al 2013). Liu et al (2014) prepared superhydrophobic and superoleophilic SiO2-modified cotton for oil/water separation via a sol-gel process, which was initially pretreated by NaOH aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a superhydrophobic surface was constructed on copper alloy sheets through immersing the substrates into the mixed solution of fluoroalkylsilane (FAS-17) molecules, ammonium persulfate ((NH 4 ) 2 S 2 O 8 ), and sodium hydroxide (NaOH) by Zhang et al 110 The obtained surface not only exhibited superhydrophobicity but also drag-reducing ability. Furthermore, some solution immersion processes may lead to the in situ growth of metal nanocrystals, which can strongly interact with low-surface-energy materials such as alkyl thiol etc., 26,27,75,120122 a new example is reported by Guo et al that reported stable superhydrophobic spongers and fabrics via immersing the substrates into a metal or transition-metal solution ( Figure 9). 26 Owing to the in situ growth of metal or transition metal oxide nanocrystals on the surface, the substrates can bond with thiols strongly.…”
Section: Grafting Coatingmentioning
confidence: 90%
“…Furthermore, some solution immersion processes may lead to the in situ growth of metal nanocrystals, which can strongly interact with low-surface-energy materials such as alkyl thiol etc., 26,27,75,120122 a new example is reported by Guo et al that reported stable superhydrophobic spongers and fabrics via immersing the substrates into a metal or transition-metal solution ( Figure 9). 26 Owing to the in situ growth of metal or transition metal oxide nanocrystals on the surface, the substrates can bond with thiols strongly. After solution immersion, the substrates may be modified by other substances to achieve functional superhydrophobicity.…”
Section: Grafting Coatingmentioning
confidence: 90%
See 2 more Smart Citations